1977
DOI: 10.1071/ar9770413
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of soil nitrogen by legumes in mixed swards

Abstract: The partitioning of uptake of soil nitrogen between legumes and grasses in mown, mixed swards was studied at two sites in south-eastern Queensland. The swards contained either Lotononis bainesii, Desmodium intortum or Trifolium repens with Digitaria decumbens at one site, and either L. bainesii, T. repens, Macroptilium atropurpureum, Vigna luteola or Stylosanthes guyanensis with Chloris gayana at the other site. (15NH4)2SO4 equivalent to c. 0.3 kg nitrogen ha-1 was added every 4 weeks in an attempt to label th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 0 publications
4
39
1
Order By: Relevance
“…This was somewhat surprising, since legumes harbor N-fixing bacteria. Melilotus officinalis likely competed most strongly for nitrogen in the early stages of its development when legumes primarily take up unfixed soil nitrogen (Vallis et al 1977) and before root nodules have developed (Wolf and Rohrs 2001). Therefore, this non-native legume competed for all the resources that we measured, even nitrogen.…”
Section: Discussionmentioning
confidence: 98%
“…This was somewhat surprising, since legumes harbor N-fixing bacteria. Melilotus officinalis likely competed most strongly for nitrogen in the early stages of its development when legumes primarily take up unfixed soil nitrogen (Vallis et al 1977) and before root nodules have developed (Wolf and Rohrs 2001). Therefore, this non-native legume competed for all the resources that we measured, even nitrogen.…”
Section: Discussionmentioning
confidence: 98%
“…However, in a mixed pasture the grass was usually more efficient at taking up fertiliser N from the soil than legumes. For example, Vallis et al (1977) showed that white clover in mixed pastures with a selection of tropical grass species rarely obtained more than 25% of the available soil N whereas Murphy & Ball ( 1985) found ryegrass accumulated more than twice the amount of nitrate as clover even when both were grown in monoculture. The more efficient use of fertiliser N by ryegrass compared with clover leads to increased ryegrass growth.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of this procedure requires that a direct N transfer does not occur during the test (McAuliffe et al, 1958). Available data from a similar experiment (Broadbent et al, 1982) suggest that, in a field situation, direct N transfer is of little importance as compared to indirect transfer, which is of no consequence (Vallis et al, 1977).…”
Section: Calculation Of N From Symbiosis and Apparent Clover-to-grassmentioning
confidence: 98%